A Learning Model Based on the Elderly Philosophy for a Happy Life in Thai Social Context - Kodsiri, Chawalit; Kaewsufong, Somwang; Mangkhang, Charin; Dibyamandala, Jarunee (Technium Social Sciences Journal, 2022)
The objectives of this research were divided into two phases: Phase 1: To synthesize and design learning activities based on the elderly philosophy for a happy life in Thai social context; the target group consisted of 8 key informants, 6 casual Informants, and 6 general informants; instruments used were an unstructured interview form, a non-participant observation form, and a diary form, data were analyzed by content analysis and thematically analysis. Phase 2: To study a learning model based on the elderly philosophy for a happy life in Thai social context, key informants consisted of 9 experts selected by purposive sampling, instruments used were a draft model and an evaluation form, data were analyzed by mean and standard deviation. The research results were as follows: Phase 1: The synthesis and designed results consisted of 4 aspects, 4 relationships, 4 developing dimensions, 5 standards, and 6 indicators in learning activities based on the elderly philosophy. Phase 2: The learning model based on the elderly philosophy for a happy life in Thai social context consisted of POCO&A+L(PAORS). The details were: a principle (P), an objective (O), conditions for achievement (C), operations and activities (O&A), and learning processes based on the elderly philosophy consisted of planning (P), action (A), organizing (O), reflection (R), and sustainability (S). The suitability and the possibility of the learning model were at the highest level (mean = 4.76 and 4.68) respectively.